2020
DOI: 10.3847/1538-3881/abc61a
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing Open Cluster Stock 2: Member Candidates and Mass Distribution with Gaia DR2 and LAMOST

Abstract: We identify 1325 member candidates of the open cluster (OC) Stock 2 using data from Gaia DR2. We use the algorithms Clusterix 2.0 and HDBSCAN to select cluster candidates and further refine the final cluster membership by defining neighbors in 5D phase space (X cp, Y cp, /ϖ, κ · μ δ /ϖ). Among these candidates, less than half have G, G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 35 publications
6
9
0
Order By: Relevance
“…The high dispersion confirms the existence of a noticeable differential reddening across the observed field, as described in previous studies (Krzeminski & Serkowski 1967;Spagna et al 2009). Indeed, our value is compatible within the errors with that mostly accepted for the cluster, E(B − V) ≈0.35 (Ye et al 2021). Alternatively, we evaluated the reddening from the colour excess definition, that is, by comparing observed and intrinsic colours for each star.…”
Section: Reddening and Sed Fittingsupporting
confidence: 69%
See 3 more Smart Citations
“…The high dispersion confirms the existence of a noticeable differential reddening across the observed field, as described in previous studies (Krzeminski & Serkowski 1967;Spagna et al 2009). Indeed, our value is compatible within the errors with that mostly accepted for the cluster, E(B − V) ≈0.35 (Ye et al 2021). Alternatively, we evaluated the reddening from the colour excess definition, that is, by comparing observed and intrinsic colours for each star.…”
Section: Reddening and Sed Fittingsupporting
confidence: 69%
“…They took high-resolution spectra of three red giants, from which they estimated a solar-like mean metallicity ([Fe/H]=−0.06±0.03) and the chemical abundances for 23 elements. Ye et al (2021) obtained a similar value ([Fe/H]=−0.04±0.15) from LAMOST mid-resolution spectra of almost 300 likely members. They also found that Stock 2 is a massive cluster (≈ 4000 M ).…”
Section: Introductionsupporting
confidence: 61%
See 2 more Smart Citations
“…We calculate neighbors for all 496,103 sources, which is defined in phase space (x, y, z, κ • µ * α /̟, κ • µ δ /̟), same as Eq. ( 1) in Ye et al (2021) and the reference therein. In short, for each source, its neighbors is defined within a radius of 15 pc in (x, y, z) and a radius of 1.…”
Section: Member Selectionsmentioning
confidence: 99%